Complete sternal cleft with tetralogy of Fallot - Debasis Das; Nilanjan Dutta; Pratik Pandey; Adhish Basu; Manish Kumar Sharma; Rangan Koley; Amitabha Chattopadhyay (Wolters Kluwer Medknow Publications, 2020)
Complete sternal cleft is a very rare congenital midline defect of the sternum. It is not uncommonly associated with intracardiac defects. We report a case of a 2-year-old child with complete sternal cleft and tetralogy of Fallot who presented with cyanotic spells. The child underwent total correction, followed by chest wall reconstruction on the next day.